1981
DOI: 10.1111/j.1476-5381.1981.tb09970.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Morphine and Methionine‐enkephalin on the Release of Purines From Cerebral Cortex Slices of Rats and Mice

Abstract: 1 Slices of cerebral cortex from Wistar rats, TO mice or C57 mice were preincubated with [3H]-adenosine, and labelled purines were subsequently released by electrical stimulation or by perfusing with ouabain, 100 pM. 2 Electrically-evoked purine release was substantially reduced when the Ca2+ concentration in the medium was lowered from 2.4 to 0.1 mM. In both rats and mice, the electrically-evoked release was increased by morphine and methionine-enkephalin (Met-enkephalin), 10 fM and in rats and TO mice by mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The adenosine receptor subtype involved in the adenosine released by morphine has not been defined though at the spinal level much of the pharmacology points to a key role for A 1 receptors (Montegazza et al, 1984;Reeve and Dickenson, 1995;Zarrindast and Nikfar, 1994). Several studies have also reported morphineinduced or enhanced release of adenosine in the brain (Fredholm and Vernet, 1978;Phillis and Jiang, 1980;Stone, 1981) but much of the behavioural interactions have been focused to addiction rather than pain. Although central administration of theophylline does not alter morphine antinociception (De Lander et al, 1992), the adenosine analogue and A 1 receptor agonist L-PIA can potentiate tolerance to the analgesic effect of morphine (Ahlijanian and Takemori, 1985).…”
Section: Adenosine a 2a Receptors And Interactions With Opioid Nocicementioning
confidence: 99%
“…The adenosine receptor subtype involved in the adenosine released by morphine has not been defined though at the spinal level much of the pharmacology points to a key role for A 1 receptors (Montegazza et al, 1984;Reeve and Dickenson, 1995;Zarrindast and Nikfar, 1994). Several studies have also reported morphineinduced or enhanced release of adenosine in the brain (Fredholm and Vernet, 1978;Phillis and Jiang, 1980;Stone, 1981) but much of the behavioural interactions have been focused to addiction rather than pain. Although central administration of theophylline does not alter morphine antinociception (De Lander et al, 1992), the adenosine analogue and A 1 receptor agonist L-PIA can potentiate tolerance to the analgesic effect of morphine (Ahlijanian and Takemori, 1985).…”
Section: Adenosine a 2a Receptors And Interactions With Opioid Nocicementioning
confidence: 99%
“…There is a large body of evidence indicating that both acute and chronic effects of opioids are partly mediated by adenosine in the central nervous system (CNS) (Sawynok, 1998). For example morphine and other μ receptor agonists were shown to enhance adenosine release from spinal cord and cortex in vitro and in vivo (Fredholm & Vernet, 1978; Phillis et al ., 1980; Stone, 1981; Sweeney et al ., 1987, 1989; Halimi et al ., 2000). In addition to its involvement in the expression of opioid‐mediated analgesia (Sawynok et al ., 1989; Keil & DeLander, 1994; Keil & Delander, 1995; Sawynok, 1998; Lavand'homme & Eisenach, 1999), a role for adenosine in the development of opioid tolerance, dependence and withdrawal has also been suggested (Kaplan & Sears, 1996; Salem & Hope, 1997, 1999; Zarrindast et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, adenosine inhibits C�2+ fluxes in neuronal tissue (Proctor and Dun widdie, 1983;Madison et al , 1987), inhibits release of excitatory amino acids (Coradetti et al, 1984;Burke and Nadler, 1988;Fredholm and Dunwiddie, 1988), and reduces formation of free radicals (Cron stein et al, 1985(Cron stein et al, , 1986. Since adenosine release is signaled by reductions in bioenergetic state and in creases in excitatory amino acids (Hoehn and White, 1990;Chen et al, 1992) and opioids (Stone, 1981), it is likely that adenosine levels will increase following trauma. Elevated adenosine may then in teract with extracellular receptors to mediate the protective actions noted here.…”
mentioning
confidence: 99%